2021
DOI: 10.1096/fj.202101121r
|View full text |Cite
|
Sign up to set email alerts
|

Two‐photon AMPK and ATP imaging reveals the bias between rods and cones in glycolysis utility

Abstract: In vertebrates, retinal rod and cone photoreceptor cells rely significantly on glycolysis. Lactate released from photoreceptor cells fuels neighboring retinal pigment epithelium cells and Müller glial cells through oxidative phosphorylation. To understand this highly heterogeneous metabolic environment around photoreceptor cells, single-cell analysis is needed. Here, we visualized cellular AMP-activated protein kinase (AMPK) activity and ATP levels in the retina by two-photon microscopy. Transgenic mice expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 67 publications
1
4
0
Order By: Relevance
“…We measured IMPDH activity from retinal lysates of wild-type mice treated with metformin and observed a substantial abrogation of IMPDH activity in metformin-treated lysates. He et al also demonstrated that the effect of AMPK activation by metformin in the retina is notably slower than other that of other AMPK activators (40), which corroborates the delay in IMPDH activity inhibition seen in our assay. These results suggest that a potent effect of metformin in the retina is inhibition of IMPDH activity, which could be through activation of AMPK.…”
Section: Resultssupporting
confidence: 88%
“…We measured IMPDH activity from retinal lysates of wild-type mice treated with metformin and observed a substantial abrogation of IMPDH activity in metformin-treated lysates. He et al also demonstrated that the effect of AMPK activation by metformin in the retina is notably slower than other that of other AMPK activators (40), which corroborates the delay in IMPDH activity inhibition seen in our assay. These results suggest that a potent effect of metformin in the retina is inhibition of IMPDH activity, which could be through activation of AMPK.…”
Section: Resultssupporting
confidence: 88%
“…41 , 42 In particular, a recent study using reporter mice showed that rods are more dependent on glycolysis than cones, which may imply that cones are more reliant on mitochondria as their energy source and therefore more susceptible to mitochondrial dysfunction than rods. 43 Taken together, we would expect more cone than rod dysfunction in patients with LHON or OPA1.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies have shown that cones are less dependent on glycolysis than rods in non‐degenerating retinas 6,14,43 . However, in models of RP, cones maintain their viability by upregulating aerobic glycolysis through stabilization of GLUT1 expression at the plasma membrane of cone photoreceptors 2,6 .…”
Section: Resultsmentioning
confidence: 98%
“…In a non-diseased rod dominant retina, it was proposed that cones may rely more on oxidative phosphorylation than on glycolysis. 6,43 A recent study using the rd10 mouse showed exogenous lactate was sufficient to promote cone survival when TCA cycle activity was boosted by overexpression of thioredoxin interacting protein (Txnip) allele. The rescue was also dependent on LDHB, which catalyzes the conversion of lactate to pyruvate.…”
Section: Rods But Not Cones Require Glut1 For Survivalmentioning
confidence: 99%
See 1 more Smart Citation